RELASI MAKNA BAHASA INDONESIA DALAM PERDAGANGAN INTERNASIONAL - Rosalina, Erlyn; Wulandari, Linda Sari; Khairas, Eri Ester (Politeknik Negeri Jakarta, 2024)
Indonesian language is an important communication tool in the context of international trade. In the field of international trade, there are various terms and vocabulary used to describe cross-border trade concepts. However, it is important to understand that the meanings of words in Indonesian language can develop and vary depending on the context in which they are used. The study of meaning in Indonesian language can take the form of meaning relations. Meaning relations emphasize the relationship and interconnection of meanings in words. The aim of this research is for readers to understand the relationship between the meaning of terms in the field of international trade and the lexical meanings contained in KBBI. The method used is a descriptive qualitative method by collecting vocabulary through the International Trade Dictionary and interpreting it by comparing the meanings contained in KBBI. There are five words, namely basis, bid, blocking, boa, and broker. The results show that there are two types of meaning relations, namely polysemy and synonymy. There are three polysemy meaning relations, namely in the words base, blocking, and boa. Meanwhile, the synonymous meaning relationship occurs in two words, namely bid and broker